Pengaruh Return On Asset (Roa), Net Interest Margin (Nim), Dan Capital Adequacy Ratio (Car) Terhadap Harga Saham Perbankan Syariah Di Indonesia Periode 2012-2015 - Pudja Alifah, Firdha; Drs. Ma'ruf, M.M (2017)
ABSTRACT This study aims to determine the effect of the Return On Asset (ROA), Net Interest Margin (NIM), and Capital Adequacy Ratio (CAR) Share Price Of Islamic Banking in Indonesia Period 2012-2015. This research is quantitative, the population used in this study is Islamic bank in Indonesia for the period 2012-2015. Samples were taken by total sampling is to use the entire population of the research samples. So the study sample to 11 Islamic Bank in Indonesia. Data used in this research is quantitative data in the form of the annual publication of financial statements issued by Bank Indonesia for four years in a row from the period 2012 to 2015. The data analysis technique used in this research is multiple linear regression. the results showed that ROA (X1) has a significance value 0101> 0.05 sehinggan ROA (X1) individually did not significantly affect the stock price (Y). NIM (X2) have a significance value 0661> 0.05 so that NIM (X2) individually did not significantly affect the stock price (Y). CAR (X3) have a significance value 0.039 <0.05 sehinggan CAR (X3) individually significant influence on stock prices (Y). Based on the test results show the value of F count regeresi of (5885) with significance 0.002 <0.05 means that together ROA (X1), NIM (X2), CAR (X3) influence on stock price (Y). Keywords: ROA, NIM, CAR, Stock Price.